Exosomes Derived From Hypertrophic Cardiomyocytes Induce Inflammation in Macrophages via miR-155 Mediated MAPK Pathway - Yu, Hui; Qin, Lei; Peng, Yunzhi; Bai, Wenhui; Wang, Zhanli (Frontiers in Immunology, 2021)
The inflammatory immune microenvironment plays an important role in the development of cardiac hypertrophy. Exosomes have emerged as the potent modulators of inflammatory responses. This study aimed to determine how exosomes derived from Angiotensin II (Ang II)-induced hypertrophic cardiomyocytes (HCs) interfere with the inflammatory signal pathways in macrophages. Herein, we showed that increased exosome release was observed in HCs when compared to normal cardiomyocytes (NCs). Incubation of the murine macrophage cell line RAW264.7 in the presence of exosomes isolated from the culture media of HCs triggers the secretion of inflammatory cytokines interleukin (IL)-6 and IL-8. Cytokines release induced by HCs-derived exosomes was prevented by down-regulation of Argonaute2 (AGO2), suggesting that the non-coding RNAs were involved in exosome-induced inflammatory responses in RAW 264.7 macrophages. RNA sequencing assays further demonstrated that a total of 7 microRNAs were differentially expressed between NCs-derived and HCs-derived exosomes. Importantly, miR-155 played a crucial role in the initiation of inflammation in macrophages. Further analyses demonstrated that HCs-derived exosomes induced the phosphorylation of extracellular signal-regulated kinase (ERK), c-Jun N-terminal kinase (JNK), and p38 via miR-155. Our results support the concept that exosomal microRNAs have emerged as important inflammatory response modulators regulating cardiac hypertrophy.